Cobalt, lead, and borax: Preliminary LA-ICP-MS and SEM-EDS analysis of Late-18th- to Mid-19th-century British refined earthenware glazes. (June 2021) - Greer, Matthew C.; MacDonald, Brandi L.; Stalla, David
Highlights: We analyzed glaze samples from 25 late-18th-to mid-19th-century British refined earthenwares from Belle Grove Plantation (Virginia, U.S.A.) using LA-ICP-MS and SEM-EDS. Results showed that each of the five major ware types during this period (creamware, pearlware, whiteware, yellowware, and ironstone) can be chemically differentiated using LA-ICP-MS. Our findings suggest that LA-ICP-MS can provide an additional way of identifying refined earthenwares that can prevent them from being misclassified and producing erroneous dates for sites and features. We identified several trends that, if validated through additional testing, can provide new insights into existing histories of late-18th-to mid-19th-century refined earthenwares. Abstract: Late-18th- to mid-19th-century British refined earthenwares are found the world over, yet these have rarely been analyzed using archaeometric techniques, and almost everything we know about differentiating and dating these ceramics comes from written documents. Through a preliminary LA-ICP-MS and SEM-EDS analysis of 25 refined earthenware glazes (five each from creamware, pearlware, whiteware, yellowware, and ironstone), we discuss the possible way historical archaeologists can expand our knowledge of these important ceramics. Specifically, our results suggest that the five most common refined earthenwares can be distinguished based on their chemical composition. Furthermore, this data allows us to engage with the existing literature in novel ways that can confirm, discount, and provide new insights into late-18th-to mid-19th-century refined earthenware glazes by assessing (dis)similarities between their colorants and fluxes.